2022
DOI: 10.3390/lubricants10120339
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Volumetric Wear of a Ball Polishing Tool Using Ultrasonic-Vibration-Assisted Polishing Process

Abstract: Ultraprecision freeform polishing using a bonnet or a felt ball mounted on a polishing head plays an important role in the mold and lens production industries. The volumetric wear of a bonnet or a felt polishing ball is still a problem to be solved. The objective of this study was to develop an ultrasonic-vibration-assisted ball polishing process on a CNC machining center to improve the surface roughness of a STAVAX mold steel and to reduce the volumetric wear of the polishing ball. The optimal combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Consequently, the fabrication of artificial joint prostheses with higher surface smoothness [ 8 ], particularly those composed of CoCrMo alloys, to minimize the generation of particles due to friction wear [ 9 ], is anticipated to significantly improve the lifespan and performance of joint prostheses. Current methods of polishing artificial joints primarily include mechanical polishing [ 10 ], electrolytic polishing [ 11 ], magnetorheological polishing [ 12 , 13 ], and ultrasonic polishing [ 14 , 15 ]. However, mechanical polishing may introduce microscopic scratches, increasing surface roughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the fabrication of artificial joint prostheses with higher surface smoothness [ 8 ], particularly those composed of CoCrMo alloys, to minimize the generation of particles due to friction wear [ 9 ], is anticipated to significantly improve the lifespan and performance of joint prostheses. Current methods of polishing artificial joints primarily include mechanical polishing [ 10 ], electrolytic polishing [ 11 ], magnetorheological polishing [ 12 , 13 ], and ultrasonic polishing [ 14 , 15 ]. However, mechanical polishing may introduce microscopic scratches, increasing surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…and ultrasonic polishing [14,15]. However, mechanical polishing may introduce microscopic scratches, increasing surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing ultrasonic-vibrationassisted technology in the finishing operations is a perspective technique for ensuring high geometrical accuracy and machined surface roughness [4]. It was reported that the roughness of the machined surface is significantly improved by ultrasonic-vibration-assisted (UVA) ball polishing from 0.122 µm to 0.022 µm [5,6]. The physical nature of UVA machining's positive effect on machined surface morphology is based on the reduction in frictional force [7].…”
Section: Introductionmentioning
confidence: 99%